International consensus conference on stool banking for faecal microbiota transplantation in clinical practice. Issue 12 (28th September 2019) - Cammarota, Giovanni; Ianiro, Gianluca; Kelly, Colleen R; Mullish, Benjamin H; Allegretti, Jessica R; Kassam, Zain; Putignani, Lorenza; Fischer, Monika; Keller, Josbert J; Costello, Samuel Paul; Sokol, Harry; Kump, Patrizia; et al.
Abstract : Although faecal microbiota transplantation (FMT) has a well-established role in the treatment of recurrent Clostridioides difficile infection (CDI), its widespread dissemination is limited by several obstacles, including lack of dedicated centres, difficulties with donor recruitment and complexities related to regulation and safety monitoring. Given the considerable burden of CDI on global healthcare systems, FMT should be widely available to most centres. Stool banks may guarantee reliable, timely and equitable access to FMT for patients and a traceable workflow that ensures safety and quality of procedures. In this consensus project, FMT experts from Europe, North America and Australia gathered and released statements on the following issues related to the stool banking: general principles, objectives and organisation of the stool bank; selection and screening of donors; collection, preparation and storage of faeces; services and clients; registries, monitoring of outcomes and ethical issues; and the evolving role of FMT in clinical practice, Consensus on each statement was achieved through a Delphi process and then in a plenary face-to-face meeting. For each key issue, the best available evidence was assessed, with the aim of providing guidance for the development of stool banks in order to promote accessibility to FMT in clinical practice.